Analysis of Locutionary Speech Acts of the Main Character in Habiburrahman El Shirazy’s Novel Bumi Cinta: a Pragmatic Study on Character Development - Azhar, Choeirul; Ridho, Muhammad; Dewi Rani Gustiasari (Sean Institute, 2025)
This study aims to analyze the forms and functions of locutionary speech acts produced by the main character, Muhammad Ayyas, in the novel Bumi Cinta by Habiburrahman El Shirazy, using a pragmatic theoretical framework. Locutionary speech acts (literal meaning) are regarded as the primary foundation for understanding a character’s utterances and the author’s strategic approach to characterization. This descriptive–analytical qualitative study employs listening and note-taking techniques to collect data in the form of Muhammad Ayyas’s utterances. The analysis reveals that locutionary speech acts are realized through three dominant sentence forms: declarative, interrogative, and imperative. Declarative locutions function to affirm the character’s principles and his intellectual–religious identity, as illustrated in utterances such as “If God wills it, anything can happen!” and “That is adultery! It is forbidden!” Interrogative locutions are strategically employed for persuasive and rhetorical purposes, as exemplified by the question, “Answer honestly, Yelena, when you were in a critical condition… whose name did you call to ask for help?” Meanwhile, imperative locutions display a spectrum of assertiveness, ranging from humanistic encouragement, such as “Come on, Dev, hurry up, stop joking around. Oh God, it is so cold, Dev,” to direct moral resistance, as seen in the utterance, “Hey devil, take your companion and leave this place.” Overall, the analysis of literal meaning through locutionary speech acts proves to be an effective key for revealing the richness and firmness of a complex and multifaceted character. This finding underscores the importance of locutionary analysis in pragmatic studies of literary texts, particularly in uncovering character construction and ideological positioning through language use.